ANALYSIS OF THE EFFECT OF CORPORATE GOVERNANCE, LEVERAGE, AND AUDIT QUALITY ON PROFIT MANAGEMENT WITH COMPANY SIZE AS A MODERATING VARIABLE ON THE GOODS CONSUMER COMPANY REGISTERED IN INDONESIA STOCK EXCHANGE (IDX) - Nurjannah, Rizka (International Journal of Public Budgeting, Accounting and Finance, 2019)
The objective of this research was to analyse the influence of Corporate Governance consisted of institutional ownership, size of board of commissioners, board of independent commissioners’ composition; leverage, and audit quality on earnings management with firm size as moderating variable in consumer goods companies listed in the Indonesia Stock Exchange. The research used associative causal method. The population was 14 companies, and all of them were used as the samples, taken by using census technique so that there were 98 observations all together. The data were gathered by conducting documentary study and analysed by using panel data regression analysis. The result of the research showed that, simultaneously, Corporate Governance consisted of institutional ownership, size of board of commissioners, board of independent commissioners’ composition; leverage, and audit quality had the significant influence on earnings management. Partially, the size of board of commissioners and leverage had the positive and significant influence on earnings management, besides institutional ownership, board of independent commissioners’ composition, audit quality had influence not significant on earnings management. The result of residual test on moderating variable showed that firm size could moderate the correlation of Corporate Governance consisted of institutional ownership, size of board of commissioners, board of independent commissioners’ composition; leverage, and audit quality with earnings management in consumer goods companies listed in the Indonesia Stock Exchange.